The Orient of Style : Modernist Allegories of Conversion - Schlossman, Beryl, 1955- (Book collections on Project MUSE., 1991)
In this study of modernist aesthetics, Beryl Schlossman reveals how for such writers as Marcel Proust, Gustave Flaubert, and Charles Baudelaire, the Orient came to symbolize the highest aspirations of literary representation. She demonstrates that through allegory, modernism became a style itself, a style that married the ancient and the modern and that emerged as both a cause and an effect, both an ideal construct and an textual materiality, all symbolized by the Orient-land of style, place of plurality, and site of the coexistence of holy lands. Toward the end of Remembrance of Things Past, t.